Types of Other People`s Speech in The Book of Milutin by Danko Popović - Dejanovic, Milica (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The subject of this paper are different types of speeches in the novel The Book of Milutin by Danko Popović. The paper provides description of different types of speeches and their modifications. Structural characteristics of direct and indirect speech of the corpus will be presented and analysed. The analysis is based on the classification first presented by Miloš Kovačević.
Keywords: types of speech; author speech; direct speech; indirect speech; The Book of Milutin; Danko Popović